2008
DOI: 10.1029/2007jd008816
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of SCIAMACHY and OMI tropospheric NO2 columns: Observing the diurnal evolution of chemistry and emissions from space

Abstract: [1] Concurrent (August 2006) measurements of tropospheric NO 2 columns from OMI aboard Aura (1330 local overpass time) and SCIAMACHY aboard Envisat (1000 local overpass time) offer an opportunity to examine the consistency between the two instruments under tropospheric background conditions and the effect of different observing times. For scenes with tropospheric NO 2 columns <5.0 Â 10 15 molecules cm À2 , SCIAMACHY and OMI agree within 1.0-2.0 Â 10 15 molecules cm À2 , consistent with the detection limits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
199
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(223 citation statements)
references
References 66 publications
(81 reference statements)
23
199
1
Order By: Relevance
“…The GEOS-Chem simulation of NO x has been evaluated extensively with in situ and satellite observations and generally agrees to within 30 % of measured NO x Hudman et al, 2007;Boersma et al, 2008b). We conducted a simulation for the year 2005 and sample the model output between 13:00 and 15:00 local time for analysis of the OMI data.…”
Section: Appendix A: Gmi Model Descriptionmentioning
confidence: 90%
“…The GEOS-Chem simulation of NO x has been evaluated extensively with in situ and satellite observations and generally agrees to within 30 % of measured NO x Hudman et al, 2007;Boersma et al, 2008b). We conducted a simulation for the year 2005 and sample the model output between 13:00 and 15:00 local time for analysis of the OMI data.…”
Section: Appendix A: Gmi Model Descriptionmentioning
confidence: 90%
“…[13] Several previous studies have used GEOS-Chem to interpret in situ measurements of reactive nitrogen Wang et al, 2004;Hudman et al, 2004Hudman et al, , 2007Martin et al, 2006] as well as observations of tropospheric NO 2 columns from satellite instruments [Martin et al, 2003a[Martin et al, , 2004bJaeglé et al, 2005;Guerova et al, 2006;Sauvage et al, 2007;Wang et al, 2007bWang et al, , 2007aBoersma et al, 2008aBoersma et al, , 2008bBucsela et al, 2008]. GEOS-Chem simulations generally agree to within 30% of measured NO x , HNO 3 , and PAN over eastern North America Hudman et al, 2007;Singh et al, 2007] [15] Figure 1 shows seasonal mean tropospheric NO 2 columns from OMI and GEOS-Chem.…”
Section: Simulation Of No 2 From Geos-chemmentioning
confidence: 98%
“…Retrievals of tropospheric NO 2 columns from GOME and SCIAMACHY have been used to demonstrate the close relationship between land surface NO x emissions and tropospheric NO 2 columns [Leue et al, 2001;Martin et al, 2003aMartin et al, , 2006Jaeglé et al, 2005;Zhang et al, 2007]. Observations of a weekly pattern in GOME tropospheric NO 2 columns with significant reductions on weekends [Beirle et al, 2003], diurnal variation in NO 2 columns driven by emissions and photochemistry [Boersma et al, 2008a], and a large increase in tropospheric NO 2 columns over eastern China inferred from GOME and SCIAMACHY [Richter et al, 2005;van der A et al, 2006] demonstrate the capability of observing air pollution from space. Petritoli et al [2004] and Ordóñez et al [2006] found a significant correlation between in situ NO 2 measurements and GOME tropospheric NO 2 columns.…”
Section: Introductionmentioning
confidence: 99%
“…GEOS data (including GEOS-5 and previous versions) have been used extensively in a variety of atmospheric chemistry investigations and have proved valuable not only in the interpretation of a wide range of atmospheric chemical measurements (6)(7)(8) but also in use of these measurements in an inverse mode to obtain improved estimates for emissions of important atmospheric species (9-11). The GEOS-5 simulation is employed here in a detailed study of the potential for globally distributed wind-generated electricity in 2006.…”
Section: Introductionmentioning
confidence: 99%